PELATIHAN MANAJEMEN PENGELOLAAN TUGAS SISWA SDI NURUL HIDAYAH MENGGUNAKAN APLIKASI GOOGLE DRIVE - Noryani Noryani; Ahmad Maulana Irfanudin; Erlita Kurniawaty; Ratih Andalusi (Universiitas Pamulang, 2021)
ABSTRACT The background of doing community service is observing and understanding the problems experienced by our community service partners, namely SDI Nurul Hidayah in the Distance Learning process during the Sars-Cov-2 virus pandemic, obstacles in the distribution of teaching materials, tasks and other activities that shift from face to face to online is a new difficulty, especially for teachers, students as well as parents and guardians of students. The purpose of this Community Service is to provide practical and efficient solutions in the distribution of subject matter using applications that are free and easy to use. The method of implementing community service is by inviting representatives from each stakeholder, namely teachers, students and representatives of parents of SDI Nurul Hidayah students in a limited emergency through the Zoom video conference application, by introducing the Google Drive application and its use practices related to the learning access process through online media. The result of the community service process is that teachers, students and parents get new experiences related to the use of online learning media, easier and more efficient distribution of teaching materials in terms of time and cost. The conclusion of this community service, namely the use of online learning media to make Teaching and Learning Activities during the pandemic can be carried out well, we suggest that as special service lecturers for community service partners so that they can increase their abilities in the field of technology, and in general so that service activities can be carried out continuously.. Keywords: Community Service, GoogleDrive, Islamic elementary school, and Nurul Hidayah ABSTRAK Latar belakang dilakukannya Pengabdian Masyarakat adalah mengamati serta memahami permasalahan yang dialami oleh mitra abdimas kami yakni SDI Nurul Hidayah dalam proses Pembelajaran Jarak Jauh di masa pandemi virus Sars-Cov-2, hambatan dalam distribusi bahan ajar, tugas serta kegiatan lainnya yang beralih dari tatap muka menjadi daring menjadi kesulitan baru khususnya bagi para guru, siswa maupun orang tua dan wali peserta didik. Tujuan dilakukan Pengabdian Masyarakat ini adalah memberikan solusi praktis dan efisien dalam pendistribusian materi pelajaran menggunakan aplikasi yang bersifat gratis dan mudah dalam penggunaannya. Metode Pelaksanaan Pengabdian Masyarakat adalah dengan mengundang perwakilan dari masing-masing stakeholder, yaitu Guru, peserta didik serta perwakilan orang tua murid SDI Nurul Hidayah secara darurat terbatas melalui aplikasi video conference Zoom, dengan memperkenalkan aplikasi Google drive serta praktik penggunaannya terkait dengan proses akses pembelajaran melalui media daring. Hasil proses pengabdian masyarakat adalah para guru, peserta didik dan orang tua mendapatkan pengalaman baru terkait penggunaan salah satu media pembelajaran daring, distribusi bahan ajar yang lebih mudah dan efisien dari segi waktu dan biaya. Simpulan pengabdian masyarakat ini yaitu penggunaan media pembelajaran daring membuat Kegiatan Belajar Mengajar selama masa pandemi dapat terlaksana dengan baik, saran kami selaku dosen pengabdi khusus untuk mitra pengabmas agar dapat meningkatkan kemampuan di bidang teknologi, dan secara umum agar kegiatan pengabdian dapat terus dilakukan secara berkesinambungan.. Kata-kata Kunci: Pengabmas, Google Drive, SDI, dan Nurul Hidayah